Loss of the laminin subunit alpha‐3 induces cell invasion and macrophage infiltration in cutaneous squamous cell carcinoma*. (1st May 2021) - Caley, M.P.; Martins, V.L.; Moore, K.; Lashari, M.; Nissinen, L.; Kähäri, V.‐M.; Alexander, S.; Jones, E.; Harwood, C.A.; Jones, J.; Donaldson, M.; Marshall, J.F.; et al.
Summary: Background: Cutaneous squamous cell carcinoma (cSCC) is a common cancer that invades the dermis through the basement membrane. The role of the basement membrane in poorly differentiated cSCC is not well understood. Objectives: To study the effect that loss of the laminin subunit alpha‐3 (α3) chain from the tumour microenvironment has on tumour invasion and inflammatory cell recruitment. Methods: We examined the role of the basement membrane proteins laminin subunits α3, β3 and γ2 in SCC invasion and inflammatory cell recruitment using immunohistochemistry, short hairpin RNA knockdown, RNA‐Seq, mouse xenograft models and patient tumour samples. Results: Analysis of SCC tumours and cell lines using antibodies specific to laminin chains α3, β3 and γ2 identified a link between poorly differentiated SCC and reduced expression of laminin α3 but not the other laminin subunits investigated. Knockdown of laminin α3 increased tumour invasion both in vitro and in vivo . Western blot and immunohistochemical staining identified increased phosphorylated myosin light chain with loss of laminin α3. Inhibition of ROCK (rho‐associated protein kinase) but not Rac1 significantly reduced the invasive potential of laminin α3 knockdown cells. Knockdown of laminin subunits α3 and γ2 increased monocyte recruitment to the tumour microenvironment. However, only the loss of laminin α3 correlated with increased tumour‐associated macrophages both in xenografted tumours and in patient tumour samples. Conclusions: These data provide evidence that loss of the laminin α3 chain in cSCC has an effect on both the epithelial and immune components of cSCC, resulting in an aggressive tumour microenvironment.